A note on Microbiological and Biochemical Evaluation of ʻOmtiganiaʼ, a Sudanese Fermented Food Based on Peanut Seed Cake (University of Khartoum Journal of Agricultural Sciences, 2022)
The objectives of this study aimed to evaluate the microbiological and biochemical changes during the fermentation of peanut                 (Arachis hypogaea) seed cake. The microflora during fermentation was dominated by a homo fermentative lactic acid bacterium (Streptococcus sp and lactobacillus sp) initially, the yeasts and mould and acetic acid bacteria were also present. The accumulation of acids led to the decline of the pH of the mixture from 5.7 to 3.6 on the seventh day of fermentation. Dried ʻOmtiganiaʼ possessed a crude protein content of 67 %. The microbiological analysis showed that the microbial population is mainly bacteria.
Keywords: seed cake,; arachis hypogaea; ʻOmtiganiaʼ; Biochemical analysis